A 30 años de la creación del Centro Interdisciplinario de Estudios de Género. Facultad de Humanidades, Universidad Nacional del Comahue (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2026)
This document presents a brief summary and historical overview of the thirty years of the CIEG.
Keywords: CIEG; 30 years; Anniversary; historical summary; feminist memory